PENERJEMAHAN CERITA RAKYAT DI OBYEK WISATA TRADISI RELIGI DI PEKALONGAN - Ayu Ida Savitri; R.A.J Atrinawati (Sabda: Jurnal Kajian Kebudayaan, 2018)
Translation is process of transferring text from source language (SL) into target language (TL).  The process can be challenging when there are no translation found on the TL as a result of different politics, economy, social, cultural, historical and religious backgrounds. A text containing folklore is one of the difficult texts to be translated as it contains legend, tradition, art or folktale. When untranslability happens, Venuti (2000: 427) suggests translator to use the original text by adding footnote or glossary. To avoid a shift in translation, Vinay and Dalbernet (1958) suggests two translation methods namely direct translation along with three translation techniques, these are Calque, and literal translation and oblique methods along with four translation techniques named transposition, modulation, equivalence or reformulation, and adaptation. This research applies those model, methods and techniques of translation along with folklore research method from Dundes (2007) to promote tourism at Pekalongan Regency area.